THE EFFECT OF SERVICE QUALITY, REPUTATION, AND WORD OF MOUTH ON INTEREST IN USING WIFI SERVICES - Sisdiyantoro, Krisan; Isro'iyah, Latifatul; Billy Prasetya Dwi Nugroho (BEMJ : Business, Entrepreneurship, and Management Journal, 2024)
This study aims to determine the effect of Service Quality (X1), Reputation (X2), Word Of Mouth (X3), on Intention to Use (Y) wifi services at BUMDes Maju Makmur Ngrance Tulungagung partially and simultaneously. This research uses a quantitative method with an explanatory type. The population in this study was obtained from the number of customers with a simple random sampling technique using the solvency formula for 50 respondents. Data collection using observation techniques, documentation, interviews, questionnaires. The results of this study indicate that there is a simultaneous influence on Service Quality (X1), Reputation (X2), and Word of Mouth (X3), on Interest in Use (Y). Through the results of the t-test Quality of Service (X1), Reputation (X2), Word of Mouth (X3) has no partial effect on the Interest in Use variable (Y).